Heritage Tourism in Singapore Chinatown: A Perceived Value Approach to Authenticity and Satisfaction. Issue 7 (1st September 2016) - Lee, Sean; Phau, Ian; Hughes, Michael; Li, Yu Feng; Quintal, Vanessa
ABSTRACT: This study examines object-based and existential authenticity using a multidimensional approach to perceived value. The effects of value perceptions on satisfaction are also examined. Data was collected from tourists at the Singapore Chinatown heritage precinct. The findings revealed that object-based authenticity, existential authenticity, and perceived monetary value positively influenced overall perceived value and subsequently, satisfaction. This paper provides researchers with a theoretical framework of authenticity and perceived value for future empirical studies in the heritage tourism context. It also provides insight into how destination marketers and policy makers can develop effective and sustainable strategies for heritage destinations.